2018
DOI: 10.5812/ijp.64638
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fecal Microbiota, Short-Chain Fatty Acids and Lactic Acid Concentrations in 5 - 8-Year-Old Children with Cow Milk Protein Allergy

Abstract: Background: Cow milk protein allergy (CMPA) has been reported to be associated with the alterations of gut microbiota. However, changes in the fecal microbial community for children aged 5 -8 years with CMPA have not been clearly elucidated. Objectives: The aim of the study is to assess the differences and relationship between fecal microbiota and levels of fecal short-chain fatty acids (SCFAs) and lactic acid in 5 -8-year-old children with CMPA, compared with the normal children. Methods: We enrolled 6 CMPA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Previous reports demonstrated a lower proportion of Ruminococcaceae in the patients with NASH compared to healthy subjects (48). Christensenellaceae, another family associated to low BMI in humans were positively correlated with total SCFAs (49). Decreased levels of SCFAs might be because of significantly higher BMI in the patients with NAFLD than the control group.…”
Section: Gut Microbiome-derived Metabolitesmentioning
confidence: 76%
“…Previous reports demonstrated a lower proportion of Ruminococcaceae in the patients with NASH compared to healthy subjects (48). Christensenellaceae, another family associated to low BMI in humans were positively correlated with total SCFAs (49). Decreased levels of SCFAs might be because of significantly higher BMI in the patients with NAFLD than the control group.…”
Section: Gut Microbiome-derived Metabolitesmentioning
confidence: 76%
“…A previous study found that Ruminococcaceae was higher in the fecal microbiome of CMPA children than in healthy children. 48 Another study found that the intestinal microbial community structure of infants with CMA was diverse, mainly in the families of Lachnospiraceae and Ruminococcaceae. 47 They also reported that Oscillospiraceae was significantly different between infants that became tolerant and those that remained allergic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of the LEfSe analysis in female and male 3xTg-AD mice at 3 and 5 months old in fecal samples, show bacteria with a statistically significant change in LDA scores such as Xanthomonadaceae , Oxalobacteraceae , Streptomycetaceae , Koribacteraceae , and Streptomycetaceae families, Gemella , Dehalobacterium , Clostridium , Allobaculum , Selenomonas , Veillonella , Lactococcus , Desulfovibrio , Bradyrhizobium , Campylobacter , Erythrobacter , Neisseria , Flexispira , Microbacterium , Collinsella , Atopobium , Pedobacter , and the S1 genera. These microorganisms have been associated with both pre-clinical models and patients who present AD mainly; however, other bacteria are related to aging, cognitive decline, cerebral damage, and inflammatory response in mice and humans ( Thomas et al, 2012 ; Wang et al, 2016 ; Bonfili et al, 2017 ; Harach et al, 2017 ; Morris et al, 2017 ; Vogt et al, 2017 ; Zhang et al, 2017 ; Aguayo et al, 2018 ; Alonso et al, 2018 ; Antonets et al, 2018 ; BĂ€uerl et al, 2018 ; Dong et al, 2018 ; Zhuang et al, 2018 ; Haran et al, 2019 ; Li et al, 2019 ; Zhan et al, 2019 ; Beydoun et al, 2020 ; Na et al, 2020 ; Westfall et al, 2020 ). These results suggest that bacteria families and genera are representative microorganisms of gut microbiota of disease that could be considered a useful tool for diagnostic as well as a progression biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%